Factors relating to depressive symptoms among elderly people with chronic vestibular dysfunction Fatores relacionados aos sintomas depressivos de idosos com disfunção vestibular crônica - Juliana Maria Gazzola; Mayra Cristina Aratani; Flávia Doná; Camila Macedo; Márcia Maiumi Fukujima; Maurício Malavasi Ganança; Fernando Freitas Ganança (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To identify factors relating to depressive symptoms among elderly people with chronic vestibular dysfunction. METHOD: This was a cross-sectional study in which 120 elderly people with chronic vestibular dysfunction answered the Geriatric Depression Scale questionnaire. Multivariate linear regression analysis was performed (p<0.05 and 95% CI). RESULTS: The patients presented a mean score of 12.86 ± 6.39 points on the Geriatric Depression Scale, and 67 of them (55.8%) scored above the cutoff of 11 points. The predictive model for worsening of depressive symptoms was composed of female gender, memory and concentration disorders, insomnia, hearing disorders, poor sight, nonuse of walking aids and greater emotional impact of dizziness. CONCLUSION: Greater numbers of depressive symptoms among elderly people with chronic vestibular disease were related to the presence of memory and concentration disorders, insomnia, hearing disorders, very poor sight, greater emotional impact of dizziness, female gender and nonuse of walking aids. OBJETIVO: Identificar os fatores relacionados aos sintomas depressivos de idosos com disfunção vestibular crônica. MÉTODO: Estudo transversal, em que 120 idosos com disfunção vestibular crônica submeteram-se ao questionário Geriatric Depression Scale. Realizou-se análise de regressão linear multivariada (p<0,05 e IC de 95%). RESULTADOS: Os pacientes apresentaram média de 12,86 ± 6,39 pontos no GDS, sendo que 67 idosos (55,8%) pontuaram acima da nota de corte 11. O modelo preditivo para piora dos sintomas depressivos foi composto por gênero feminino, distúrbios de memória e da concentração, insônia, hipoacusia, visão péssima, não utilização de dispositivo de auxílio à marcha e maior impacto da tontura no aspecto emocional. CONCLUSÃO: O maior número de sintomas depressivos de idosos vestibulopatas crônicos está relacionado à presença de distúrbios de memória e da concentração, insônia, hipoacusia, visão péssima, maior impacto da tontura no aspecto emocional, gênero feminino e não utilização de dispositivo de auxílio à marcha.